Surface electromyographic activity of trunk muscles during trunk control exercises for people after stroke; effect of a mobile and stable seat for rehabilitation. - Michelle C Haas; Bettina B Sommer; Samuel Karrer; Matthias Jörger; Eveline S Graf; Martin Huber; Daniel Baumgartner; Jens Bansi; Jan Kool; Christoph M Bauer (PLoS ONE, 2022)
The aim of this study was to explore differences in trunk muscle activity on a stable and mobile seat for people after stroke and healthy participants. Trunk control exercises are known to have a beneficial effect on trunk control, balance, and mobility after stroke. The effect of such exercises could be enhanced by the use of a mobile seat to provide further training stimuli. However, little research on the musculoskeletal effects of trunk training on mobile seats has been carried out. On a stable and a mobile seat, thirteen people after stroke and fifteen healthy participants performed two selective trunk control exercises, which were lateral flexion initiated by the pelvis and the thorax. The maximal surface electromyography relative to static sitting of the muscles multifidus, erector spinae, and obliquus externus was recorded bilaterally. The effects of group, seat condition, trunk control exercise, and muscle side were investigated employing within-subject linear-mixed-models. Compared to the stable seat, the maximal muscle activity of people after stroke on the mobile seat was higher during the thorax-initiated exercise and lower during the pelvis-initiated exercise. Healthy participants showed opposite results with higher muscle activity on the mobile seat during the pelvis-initiated exercise. For trunk control training on a mobile seat with high muscle activation people after stroke should perform trunk control exercises initiated by the thorax, for training with lower muscle activity people after stroke should initiate selective trunk movements by the pelvis. The results can support the planning of progressive trunk control rehabilitation programs.